2008
DOI: 10.1002/j.2158-1592.2008.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Capital: The Impact of Structural and Relational Linkages on Firm Execution and Innovation

Abstract: Firms invest millions of dollars annually in developing their supply chains, with the broad goal of increasing their own performance. However, despite the significant resources deployed for supply chain development, the extent to which initiating, maintaining, and managing supply chain relationships contributes to firm success remains unclear. The current article provides conceptual development supporting the valuation of firm‐to‐firm supply chain connections from the perspective of the focal firm. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
223
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(243 citation statements)
references
References 52 publications
(103 reference statements)
2
223
0
8
Order By: Relevance
“…Our research model examines the relationship between the supply chain social capital and firm performance. Previous studies examining this relationship have suggested that the social capital between organisational members within the firm is related with firm performance (Zaheer et al, 1998;Uzzi and Gillespie, 2002;Moran, 2005;Autry and Griffis, 2008;Min et al, 2008;Bernardes, 2010).…”
Section: Supply Chain Social Capital -Firm Performancementioning
confidence: 97%
See 2 more Smart Citations
“…Our research model examines the relationship between the supply chain social capital and firm performance. Previous studies examining this relationship have suggested that the social capital between organisational members within the firm is related with firm performance (Zaheer et al, 1998;Uzzi and Gillespie, 2002;Moran, 2005;Autry and Griffis, 2008;Min et al, 2008;Bernardes, 2010).…”
Section: Supply Chain Social Capital -Firm Performancementioning
confidence: 97%
“…The social capital concept in supply chain management field has been used from the end of the 2000s (Autry and Griffis, 2008;Min et al, 2008;McGrath and Sparks, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gellman (1986) examined innovative performance of railroads under deregulation and found regulation, labor influence and lack of channel member innovation as barriers to innovation in the allied industry. Autry and Griffis (2008) using social network theory propounded structural capital, relational capital and supply chain knowledge development to be positively associated with innovationoriented performance. Wagner (2008) proposed a model of logistics innovation consisting of several related activities like internal search and deve lopment, external search and development, investment in infrastructure and capital goods, acquisition of knowledge and training and education etc.…”
Section: Supply Chain Innovationmentioning
confidence: 99%
“…In the cloud computing environment, according to the different mode of construction and service, regional logistics information platform can be realized by following the 3 modes [12,13], i.e. logistics operation mode based on public cloud, logistics operation mode based on the private cloud and logistics operation mode based on hybrid cloud.…”
Section: Comprehensive Comparison and Analysis Of The Operation Modementioning
confidence: 99%